Origin of Gravitation and Description of Galaxy Rotation in a Fundamental Bound State Approach (Global Journal of Science Frontier Research, 2018)
Abstract not found
Keywords: description of gravitational systems as magnetic binding of many (e-p) pairs quantitative account of the rotation profiles of galaxies; giving rise t